LEPIOTA VIRIDITINCTA (BERK. & BROOME) SACC.: A SPECIES FROM BALI WITH GREY-GREEN COLOUR CHANGING WHEN DRIED - Atik Retnowati (Floribunda, 2015)
Lepiota viriditincta (Berk. & Broome) Sacc., a species which turns grey-green when dried, was collected from Bali. Description, images, and line drawing are provided for this newly recorded mycobiota from Indonesia.